Diagnostic Limitations of Applying a Human Portable Blood Glucose Meter in the Detection of Hypoglycemia in Pregnant Ewes - José Lucas Xavier Lopes; Raquel Fraga e Silva Raimondo; Luiza Rodegheri Jacondino; Beatriz Riet Correa; Clara Satsuki Mori; Álan Gomes Pöppl (Veterinary Sciences)
Pregnant ewes are susceptible to hypoglycemia and ketosis; therefore, monitoring glycemic status is extremely important. Portable blood glucose meters (PBGMs) can assist in quickly and conveniently identifying glycemic disturbances in this species, provided that they meet the criteria of analytical accuracy. This study evaluated the performance of a human PBGM (Accu-Chek Performa®, Roche Diagnostics, Basel, Switzerland) in the glycemic evaluation of 34 pregnant ewes at days 90 and 120 of pregnancy in comparison with the results of glycemia determination by a reference method (RM). The device showed a high positive correlation (r = 0.71, 95%CI = 0.57–0.82, p < 0.0001) with the RM; however, 96.6% of the PBGM results (58.5 ± 9.82 mg/dL) were higher (p < 0.0001) than those obtained in the laboratory (48.6 ± 9.31 mg/dL). The PBGM tested was considered analytically inaccurate according to ISO 15197:2013, which states that when glucose levels are below 100 mg/dL, 95% of the measurements should deviate by no more than 15 mg/dL from the RM value, and 1/3 of the PBGM results were above this limit. Hypoglycemia (<50 mg/dL) was documented in 60.29% of samples tested on with the RM, but only 17.64% of results were below 50 mg/dL using the PBGM. Due to these limitations, Accu-Check Performa® results should be interpreted cautiously in pregnant sheep suspected of hypoglycemia.